2013
DOI: 10.3109/0886022x.2013.829407
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between apolipoprotein E gene polymorphism with triglyceride level in patients with renal diseases

Abstract: Apolipoprotein E (apoE), one of the major plasma lipoproteins, plays a major role in the transport and metabolism of lipids by acting as a ligand. apoE gene contains three potential alleles: e2, e3 and e4, forming six genotypes: E2E2, E2E3, E2E4, E3E3, E3E3 and E4E4. Association between apoE gene polymorphism and triglyceride (TG) is still controversial. There was no any meta-analysis to explore the association of apoE gene polymorphism with triglyceride level, and this meta-analysis was performed to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Nevertheless, some studies have reported positive findings, particularly for the ε4 variant. Dong et al (2013) showed that ε4 was associated with higher triglyceride levels in patients with renal disease [ 35 ]. Carvarlho-Wells et al (2010) reported that ε4 carriers have higher postprandial triglyceride levels only in adults aged >50 years [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some studies have reported positive findings, particularly for the ε4 variant. Dong et al (2013) showed that ε4 was associated with higher triglyceride levels in patients with renal disease [ 35 ]. Carvarlho-Wells et al (2010) reported that ε4 carriers have higher postprandial triglyceride levels only in adults aged >50 years [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang Y et al proved that hemodialysed ε4 allele carriers have higher total cholesterol (TC), TG, and LDL-C [27]. ε2 allele carriers develop accumulation of cholesterol-rich VLDL [28]. However, there is poor knowledge about the relationship between APOE gene polymorphism, APOE level, its distribution among lipoproteins and the degree of kidney dysfunction, especially at early stages of CKD.…”
Section: Introductionmentioning
confidence: 99%